Linking Foraging Behaviour and Habitat Preferences During Moult Across Multiple Populations of Red‐Throated Diver - James Duckworth; Susan O'Brien; Ruth E. Dunn; Ib K. Petersen; Aevar Petersen; Guðmundur Benediktsson; Logan Johnson; Petteri Lehikoinen; David J. Okill; Roni Väisänen; Jim Williams; Stuart Williams; et al. (Ecology and Evolution)
ABSTRACT Understanding the habitat use of individuals can facilitate methods to measure the degree to which populations will be affected by potential stressors. Such insights can be hard to garner for marine species that are inaccessible during phases of their annual cycles. Here, we quantify the link between foraging habitat and behaviour in an aquatic bird of high conservation concern, the red‐throated diver (Gavia stellata) across three breeding populations (Finland, Iceland and Scotland) during their understudied moult period. Specifically, we quantify the relationship between feather isotope values (δ13C and δ15N) and diving behaviour, within and between populations, examining the use of intra‐depth zone (IDZ) dives as a proxy for benthic foraging. We found a strong positive relationship between both higher δ15N values and, to a lesser extent, δ13C values and the proportion of IDZ dives. This relationship was consistent across all three populations, but the baseline δ13C values varied between them, indicative of the populations' different moulting areas. Our results demonstrate that red‐throated divers continue to be generalist foragers after their breeding seasons, and that behavioural flexibility varies within and between populations. Furthermore, due to the existence of these relationships, we reveal the potential of stable isotope analysis as a standalone tool for monitoring changes in habitat use in this ecologically significant species. The approach may also apply to other generalist foragers that are known to use multiple foraging strategies (e.g., foraging benthically and pelagically), with implications for future conservation efforts.